Potential Antibacterial Activity of Two Important Local Chewing Sticks “Fagara zanthoxyloides and Distemonanthus benthamianus” along with Antioxidant Capacities - Shittu, AO; Aliyu, A; David, MS; Njinga, NS; Ishaq, HI (Dhaka University Journal of Pharmaceutical Sciences, 2019)
In order to authenticate and ascertain the various claim by the rural dwellers that depend on chewing sticks for their oral hygiene and protection against innumerable diseases, the antibacterial activity of the roots of Fagara zanthoxyloides and Distemonanthus benthamianus were evaluated. Preliminary phytochemical screening was carried out using standard methods. In-vitro antibacterial activity of the methanol extracts of both plants was also carried out using the agar well diffusion method against standard strains of Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Salmonella typhii ATCC 14028, Citrobacter freundii ATCC 8090 and also some clinical isolates of Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis at different concentrations and ratios. Preliminary phytochemical screening showed that the extracts contained alkaloids, saponin, tannins, steroids, flavonoids, anthraquinones, cardiac glycosides and phenol. All the test microorganisms were susceptible to the inhibitory effect of the extracts at concentrations of 200 mg/ml and 500 mg/ml. F. zanthoxyloides had better antimicrobial activity with zones of inhibition ranging from 21.0 to 26.0 mm at 200 mg/ml and 24.3 to 29.3 mm at 500 mg/ml while D. benthamianus had zones of inhibition ranging from 17.7 to 26.7 mm at 200 mg/mL and 19.0 to 26.7 mm at 500 mg/mL. Some of the test microorganisms were resistant to the standard antibiotics (cefuroxime, ciprofloxacin, ofloxacin and gentamicin). Combinations of the extracts in ratios 50:50 and 75:25 yielded no increase in activity. The MIC and MBC for D. benthamianus ranged from 6.25 mg/ml to 100 mg/mL and 25 to 200 mg/ml, respectively while that of F. zanthoxyloides ranged from 1.56 mg/ml to 12.5 mg/mL and 50 to 200 mg/ml, respectively. The antimicrobial activity demonstrated by F. zanthoxyloides and D. benthamianus indicates that they would be valuable in the management of urinary, respiratory and gastrointestinal tracts infections while at the same time helping to mitigate the problem of antimicrobial resistance. Phenolic compounds of plants, among them flavonoids are the chief constituents, which have potent antioxidant activities Dhaka Univ. J. Pharm. Sci. 18(2): 223-232, 2019 (December)